RIVERS AND RIVER ESTUARIES IN SRI LANKA: AN INTERPRETATION - Jinadasa Katupotha; Sachith Gamage (Malaysian Journal of Tropical Geography (MJTG), 2025)
Sri Lanka’s river systems are essential to the nation’s geomorphological, ecological, and socio-economic fabric. Despite their significance, the country’s river classification and drainage mapping have long been misrepresented, particularly the misconception that Sri Lanka possesses 103 river basins flowing radially from the Central Highlands. This study addresses this critical research gap by revaluating and redefining Sri Lanka’s true drainage systems, origins, and outflow characteristics through comprehensive geomorphological and hydrological analysis. The primary aim of this research is to provide an accurate interpretation of rivers and river estuaries in Sri Lanka by integrating field investigations, geomorphic mapping, and digital elevation models (DEMs). The specific objectives are to (1) correct long-standing misinterpretations regarding river basin classification and drainage patterns, (2) identify the true number and distribution of rivers that directly discharge into the Indian Ocean, (3) categorize the types of river estuaries based on geomorphological and hydrological parameters, and (4) examine the implications of human interventions, such as dams and diversions, on natural flow regulation and estuarine dynamics. Using SRTM derived DEMs, topographic contour analyses, and field validation across 29 major river outlets, the study reveals that Sri Lanka comprises 94 true river basins, of which only 29 rivers directly discharge into the Indian Ocean. These outlets form five distinct estuarine types: drowned river valleys, bar-built perennial, bar-built seasonal, perennial delta, and seasonal delta estuaries. Contrary to previous literature, only eight of these rivers originate above the 1200 m contour line of the Central Highlands, while the majority emerge below it. The findings underscore the necessity of reinterpreting Sri Lanka’s fluvial and estuarine systems for accurate hydrological assessment, policy formulation, and sustainable water management. Recognizing the spatial and functional diversity of these systems is vital for ecological conservation, flood control, agricultural planning, and the preservation of cultural heritage linked to ancient hydraulic civilizations. This reinterpretation provides a scientifically grounded framework to guide future research and national resource management strategies concerning Sri Lanka’s riverine landscapes.